Possibilities of general manual lymphatic drainage correction as a part of complex therapy of myofascial pain syndrome in athletes - A. S. Mogelnitskiy; O. A. Churganov; A. G. Shchurov; A. A Yakovlev (National Electronic Information Consortium (NEICON), 2021)
The article describes the general principles of manual lymphatic drainage correction. The authors evaluated the effectiveness of its application in the complex therapy of recreational rehabilitation of athletes with myofascial pain syndrome (MPS).Objective: to evaluate the effectiveness of general manual lymphatic drainage correction in the treatment of athletes with MPS.Materials and Methods: a total of 30 rugby players were examined. All athletes from the main group received physiotherapy, general lymphatic drainage massage. Patients from the control group underwent the same procedures and general massage without lymphatic drainage correction. The course of therapy included 6 procedures.Results: tensoalgometric parameter values in athletes from the main group increased by more than 5 times after lymphatic drainage correction. In sportsmen from the control group, these parameter values decreased.Conclusion: the application of manual lymphatic drainage contributes to the active restoration of myotatic reflex of physical muscles and regress of pain syndrome in athletes.